Bounding the frontiers: An assessment of the Gaza’s relations with the Hlengwe of Zimbabwe (1835–1895) - Mathebula, Mandla M. (Contree, 2024)
The Hlengwe people of southeastern Zimbabwe are one of the sub-groups of the Tsonga people who straddle parts of Mozambique, South Africa, Zimbabwe and Swaziland. In Zimbabwe, they constitute the only Tsonga group resident there. Like other sub-groups of the Tsonga, orthodox paradigm of their history suggests that they were once attacked, defeated and subjugated by the Gaza of Soshangane. Alternatively, they are said to have been forced to pay tribute to the Gaza which on its own is incorrectly viewed as subjugation. As a result, they are assumed to have been subjugated by the Gaza during the latter’s dominance of southern Mozambique and eastern parts of Zimbabwe. Consequently, they are referred to as Shanganes, the name applied to people who were part of the Gaza under Soshangane and his successors. This article investigates the Gaza’s and the Hlengwe’s movements and activities to determine if indeed the two groups’ interactions resulted in the Gaza’s subjugation of the Hlengwe. In a broader sense, it looks at the manner in which the borders of the Gaza are often overstated. Contribution This work contributes to the body of knowledge in the field of African history, especially minority groups.